Comparison between Round Robin and Virtual Migration Algorithm Based on their Energy Efficiency - Akilasri, P.S.S; Meenakshi, K (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is an important field in today’s computer world. Data are entered the server through various algorithms and each algorithm has its own advantages and disadvantages. In this paper two algorithms are compared, and their energy efficiency based on their time taken is found and a graph is tabulated. The algorithms are Round Robin and Virtual Machine migration algorithms